Influence of gas-to-liquid fuel in the combined blends of biodiesel-diesel / Sajjad Hossain - Sajjad, Hossain (2015)
Energy security concerns and environmental sustainability issues have been increasing with the growth of civilization, which have developed the urge to increase energy efficiency with a diminution in environmental pollution. These situation have stimulated the researchers to focus on the alternative transportation fuels like Gas-to-liquid (GTL) fuel and biodiesel. GTL fuel is produced from Fischer–Tropsch synthesis and consists of some distinctive characteristics such as its paraffinic nature, very low sulfur and aromatic contents and a high cetane number. It can be used as an alternative to diesel and also with the blends of diesel and bio-diesel. Biodiesels are mono-alkyl esters of fatty acids, which can be produced from several widely available feedstock and consist of special features like renewability and diminution of engine emissions, which make those as one of the most potential substitutes for diesel or with the blends with diesel.